التداعيات السياسية والأمنية والاقتصادية على الاتحاد الأوروبي جراء بريكست - دخيلد. سالم علي (Aljameai, 2023)
المستخلص: في عام 1961 تقدمت بريطانيا بطلب انضمامها إلى الاتحاد الأوروبي وقوبل طلبها بالرفض من قبل شارل ديغول الرئيس الفرنسي آنذاك خوفاً من التقارب البريطاني الالماني ، وبعد استقالة ديغول في 1969 ، فتح المجالي للتفاوض لانضمام بريطانيا للتكتل الاوروبي وتم قبول انضمامها إلى الاتحاد في العام 1973 بشكل رسمي. وفي عام 2016 قررت بريطانيا إعادة النظر في عضويتها في الاتحاد الاوروبي من خلال استفتاء شعبي نتج عنه التصويت لصالح خروج بريطانيا من الاتحاد الاوروبي مما أثر على مكانتها في الساحة الدولية وكقطب سياسي وموحد للاتحاد. ومن خلال هذه الدراسة سوف اتناول التداعيات السياسية والامنية والاقتصادية التي سببها خروج بريطانيا من الاتحاد الاوروبي. Abstract: In 1961, Britain applied to join the European Union, but its request was rejected by Charles de Gaulle, the French President at the time, for fear of British. German rapprochement. After De Gaulle’s resignation in 1969, the way was opened for negotiations for Britain’s accession to the European bloc, and its accession to the European Union was officially accepted in 1973. In 2016, Britain decided to reconsider its membership in the European Union trough a popular freedom that resulted in a vote in favor of Britain’s exit From the European Union, which affected its position in the international arena and as political and unifying Pole for the union.